Development of Textbook Based on Character Using Multimedia to Improve Critical Thinking Skills for Elementary School Students - Hendratno; Fajar Nur Yasin; Suprayitno; Nurul Istiq’faroh (Studies in Learning and Teaching, 2023)
This research and development aims to produce character-based textbooks using multimedia that are of good quality in terms of validity, practicality, and effectiveness that can improve students' critical thinking skills. The research adopted the 4D model, which consists of four stages: define, design, develop, and disseminate. Data were collected through expert validation questionnaires, observation sheets of teacher and student activities, student response questionnaires, and critical thinking tests (pretest and posttest). The results of the study indicated that: (1) the character-based textbooks were highly appropriate, (2) the textbooks were found to be highly practical based on observations of teacher and student activities and received very positive feedback from students, (3) the textbooks were effective in improving critical thinking skills, as demonstrated by the medium category of n-gain on the critical thinking test and the posttest average score being higher than the pretest average score. This character-based textbook can assist teachers in instilling character and improving critical thinking skills in fourth grade elementary school students.